Advanced Database Strategies for Multi-Location Environments: Privacy, Security, and AI Integration - Ramachandran, Karthick (International Journal of Scientific Research and Management (IJSRM), 2025)
In an increasingly globalized and data-driven world, enterprises with multi-location operations face significant challenges in managing distributed data securely, reliably, and efficiently. This paper presents a comprehensive framework for modern database architectures optimized for privacy, security, performance, and AI integration. We propose an intelligent hybrid model combining localized edge databases and centralized data platforms with robust replication, autonomous management, and encryption mechanisms. The architecture supports business intelligence, custom reporting, third-party data sharing, and future-resilient cryptographic standards. Concepts such as fully homomorphic encryption, secure multi-party computation, differential privacy, and quantum-safe cryptography are explored to ensure regulatory compliance and operational integrity. While the principles are industry-agnostic, their implementation is illustrated in the context of the highly regulated and transaction-intensive casino industry. This research bridges academic theory and applied innovation, proposing advanced database paradigms to support the evolving demands of secure, scalable, and intelligent enterprise data ecosystems.